INTEGRATION OF CHARACTER EDUCATION VALUES IN ISLAMIC RELIGIOUS EDUCATION LEARNING AT SCHOOL - Alfarisy, Shofwatunnida Julia; Iswandi (PT. Jurnal Center Indonesia Publisher, 2025)
Islamic values-based character education has an important role in shaping the morality and ethics of students in schools. However, the implementation of character education in Islamic Religious Education learning still faces various challenges, such as the lack of integration in the curriculum, ineffective learning methods, and the lack of parental and community involvement. This study aims to analyse the integration strategy of character education values in Islamic Religious Education learning in schools through a literature study approach. The method used is library research, by reviewing various scientific journals, academic books, and relevant policy documents. The results show that Islam-based character education can be effectively implemented through several strategies, namely affective approaches in teaching, integration of character values in the curriculum and extracurricular activities, active involvement of parents and communities, and habituation of Islamic values in school life. In addition, the role of teachers as role models and creators of a conducive learning environment determine the success of character education. The conclusion of this study confirms that effective character education requires a comprehensive and sustainable approach so that students can internalise Islamic values in their daily lives. The findings are expected to be a reference for educators and policy makers in developing more effective learning models in instilling Islamic-based character in schools.